Role of the cytoplasmic domains of viral glycoproteins in antibody-induced cell surface mobility. - Lydy, S L (1993)
We have investigated the role of the cytoplasmic domains of the influenza virus hemagglutinin (HA) and the parainfluenza virus type 3 (PI3) fusion (F) glycoproteins as a determinant of their ability to undergo antibody-induced redistribution on plasma membranes. The viral envelope genes were truncated in their cytoplasmic domains by using oligonucleotide-directed mutagenesis and expressed by using recombinant vaccinia viruses. In HeLa cells, the truncated HA (HAt), like the full-length HA, did not cap in response to specific antibody. In CV-1 cells, HAt showed patchy surface immunofluorescence with few caps, whereas full-length HA exhibited capping in many cells in response to bivalent antibody. Quantitation of cap formation indicated a sevenfold decrease in the frequency of capping of HAt in comparison with full-length HA. Similarly, truncated F also exhibited a significant decrease in cap formation in comparison with full-length F. These results indicate that the ability of influenza virus HA and PI3 F to undergo redistribution in response to bivalent antibody has been altered by truncation of the viral glycoproteins and suggest that capping may involve interactions between the cytoplasmic domain of the viral glycoproteins and host cell components.